Critical success factors for knowledge repository implementation: Content, technology and promotion - Norfatin Farhanah Zamani; Tengku Adil Tengku Izhar (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
Knowledge repository is a computerized system that maintains various digital resources to be accessed by the users electronically. Critical success factor on the other hand is defined as the crucial elements that contribute to the success of an event or organization. This paper reviews the literatures on the contributing factors of knowledge repository implementation among the users which specifically focus on the content coverage, technological function and promotion of knowledge repository besides discussing on the proposed models on the critical success factors of knowledge repository. This paper aims to study the factors that are critical or contribute to the success of knowledge repository implementation. This study is significant to the top management and employees of an organization for improving the knowledge repository service in the organization which may act as an effective tool towards the enhancement of the organization performance.
Keywords: 650; Content coverage; Critical success factors; Knowledge repository; Promotion; Technological function